Annulus Fibrosus Repair Using High-Density Collagen Gel: An In Vivo Ovine Model. Issue 4 (15th February 2018) - Pennicooke, Brenton; Hussain, Ibrahim; Berlin, Connor; Sloan, Stephen R.; Borde, Brandon; Moriguchi, Yu; Lang, Gernot; Navarro-Ramirez, Rodrigo; Cheetham, Jonathan; Bonassar, Lawrence J.; Härtl, Roger
Abstract : Study Design: Ovine in vivo study. Objective: To perform lateral approach lumbar surgery in an ovine model to administer an injectable riboflavin cross-linked high-density collagen (HDC) gel and to assess its ability to mitigate intervertebral disc (IVD) degeneration after induced annulus fibrosus (AF) injury. Summary of Background Data: Biological-based injectable gels have shown efficacy in restoring biomechanical, radiographic, and histological parameters in IVD-injured animal models. Riboflavin cross-linked HDC gel has previously demonstrated retention of nucleus pulposus (NP) tissue, reduced loss of disc height, and prevention of terminal cellular degenerative changes in rat-tail spines. However, this biological therapy has never been tested in large animal models. Methods: Forty lumbar IVDs were accessed from eight sheep via lateral approach surgery. IVDs were randomly assigned to healthy control, injury and HDC treatment, or negative control with injury and no treatment. IVD injury was carried out using a drill-bit through the AF followed by needle puncture of the NP. Sheep were followed for 16 weeks and underwent qualitative/quantitative magnetic resonance imaging, x-ray, and histological analyses of collagen and proteoglycan content. Results: The lateral approach to the ovine lumbar spine to deliver HDC gel proved to be safe and reproducible. IVDs treated with the HDC gel revealed less degenerative changes at the microscopic level based on AF and NP histology. However, mean Pfirrmann grade, T2 relaxation time, NP voxel size, and disc height index were not significantly different between the two injury groups. Conclusion: Injectable HDC gel can be administered safely via lateral approach surgery in an ovine AF injury model. IVDs treated with HDC gel demonstrated less degeneration at the microscopic level though radiographic changes were slight when comparing treated to untreated IVDs. Future studies will need to elucidate the role of injury technique and time frame for follow-up in correlating histological and radiographical outcomes. Level of Evidence: N /A Abstract : Supplemental Digital Content is available in the text